Detecting the polymorphism of TERF1 gene by an improved PCR‐RFLP method. Issue 1 (23rd February 2017) - Wang, Pengpeng; Yang, Yongli; Wang, Sihua; Duan, Xiaoran; Wang, Tuanwei; Feng, Xiaolei; Yan, Zhen; Wu, Yongjun; Yu, Songcheng; Wang, Wei
Abstract : Background: Polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP) is a common and mature method of detecting the single nucleotide polymorphism (SNP). But, for the polymorphism site rs3863242 of telomeric repeat binding factor 1( TERF1 ) gene, there is no appropriate restriction enzyme to recognize it, which limits the research between the variants of rs3863242 and human diseases. Methods: The reverse primer was designed based on turning the 3rd base T into the mismatch base G. After PCR amplification, a new restriction enzyme site was introduced into the TERF1 gene amplification products. Two hundred forty samples from Chinese Han individuals were genotyped to evaluate this method. Results: A new restriction enzyme site for Cvi QI was introduced into the PCR products. The genotype frequencies of 240 samples from Chinese Han individuals were 4.17% for A/A, 29.58% for A/G, 66.25% for G/G respectively. The allele frequencies were 18.96% for A and 81.04% for G respectively. The genotyping results of PCR products were consistent with the gene sequencing result. Conclusions: We developed a simple, direct and economical technique for analyzing the polymorphism of TERF1 rs3863242. It may be applied to the colony screening of other SNPs, mutation‐screening of tumor‐related gene or mutations in some specific genes on a large scale, in the future.